Evolutional levels and professionalization of administration - Калашнікова, Світлана (Educological discourse, 2013)
The article is devoted to the analysis of upbringing the theory of administration and its influence to the context of the process for professionalization of administration, which is realized through professional development of administrators, forming the administrative infrastructure and forming conception of the world-view the form of philosophy of governance.